Finite Element Simulation of the Instrumented Indentation Test to Estimate the Mechanical Properties for ASTM516-G70 and AISI1010 steels - Elmisteri, Ahmed. F.; Midawi, Abdelbaset R. H.; Shuaeib, Farag M (Al-Mukhtar Journal of Sciences, 2019)
Instrumented indentation technique at micro-scales has become more popular to determine mechanical properties of materials like hardness, modulus of elasticity, and yield strength. It is introduced as a method that finds the stress-strain curve, instead of the traditional tensile test. Furthermore, it gives a possibility to determine the mechanical properties for small specimens and material under operation in the field. Several researchers have attempted to evaluate this method experimentally and to investigate the factors affecting it by using a different shape of indenters, and different types of materials. In the same regard, this research work is conducted to evaluate this method experimentally and by finite element simulation methods. Two types of industrially significant steels were selected; they are namely ASTM516-G70, AISI1010 steel; and two shapes of indenters, blunt and sharp (Spherical, and Vickers) were used. The finite element simulation has been performed by ABAQUS simulation program, and its results were then compared with the experimental test results obtained from Nanovea instrumented indentation test machine. The results obtained have demonstrated good agreement between the experimental and the finite element simulation results within 5 % difference for young’s module, and 7.7 % for yield strength whereas excellent agreement is observed in the elastic region and the beginning of the plastic region for the engineering stress-strain curve. Finally, it is to be emphasized that the obtained results are more applicable for the tested materials, and further research is recommended to accommodate other materials as well and to confirm the generality of this method.